Challenging the profanity of management of higher education - Degn, Lise; Glavind, Johanne Grøndahl; Pechmann, Philipp; Fuglsang, Simon (Journal of Praxis in Higher Education, 2024)
Management and managerialism in higher education have become increasingly synonymous with the corruption of self-regulating institutions, with the disbandment of collegial governance, and with a general devaluation of traditional academic norms and values; they have become profane concepts. In this paper, this profanity is challenged, through an exploration of its reach into the actual practices of higher education. We conceptualise two versions of profane management: management as discursively profane and as practically profane. Using data from a Delphi study on perceptions of quality and quality management, we explore the usefulness of these concepts and discuss their value.